The immigrant-native wage gap in Germany revisited - Kai Ingwersen; Stephan L. Thomsen (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This study provides new evidence on the levels of economic integration experienced by foreigners and naturalised immigrants relative to native Germans from 1994 to 2015. We decompose the wage gap using the method for unconditional quantile regression models by employing a regression of the (recentered) influence function (RIF) of the gross hourly wage on a rich set of explanatory variables. This approach enables us to estimate contributions made across the whole wage distribution. To allow for a detailed characterization of labour market conditions, we consider a comprehensive set of socio-economic and labour-related aspects capturing influences of, e.g., human capital quality, cultural background, and the personalities of immigrants. The decomposition results clearly indicate a significant growing gap with higher wages for both foreigners (13.6 to 17.6 %) and naturalised immigrants (10.0 to 16.4 %). The findings further display a low explanation for the wage gap in low wage deciles that is even more pronounced within immigrant subgroups. Cultural and economic distances each have a significant influence on wages. A different appreciation of foreign educational qualifications, however, widens the wage gap substantially by 4.5 ppts on average. Moreover, we observe an indication of deterioration of immigrants' human capital endowments over time relative to those of native Germans.
Keywords: J61; J31; J15; 330; immigration; wage gap; unconditional quantile regression; Germany